The Public Trust Doctrine And Legislative Inertia: Reimagining India’s Statutory Environmental Framework (International Journal of Environmental Sciences, 2025)
The public trust doctrine has emerged as a foundational principle in environmental jurisprudence worldwide, positing that certain natural resources are held by the state in trust for the public. In India, this doctrine has been invoked by courts as a tool of environmental protection, raising the question of whether it stands as a codified ideal or a construct of judicial innovation. This paper highlights how the doctrine has been woven into India’s Article 21[i] Jurisprudence via judicial activism and explores the tension between this judge-made principle and the country’s statutory environmental framework. The discussion also flags the notable reluctance of the Indian legislature to codify the doctrine, setting the stage for a comparative look at other jurisdictions (such as South Africa and Australia) to contextualize India’s approach and incorporate best practices into the domestic jurisdiction.